State and Market in Higher Education Reforms Trends, Policies and Experiences in Comparative Perspective - Schuetze, Hans G.; Mendiola, Germán Álvarez; Conrad, Diane (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Universities have never been static. Even so, it is fair to say they have experienced a most radical transformation in the past twenty years. During this period, the role and responsibility of the state generally have been broadly limited while allowing ‘market forces’--private ownership and control--more influence. But even where the state is still the main provider or funder, it relies increasingly on ‘market mechanisms’, for example contractual relations between state and institutions, competition among providers for resources, and external assessment of ‘outputs’ which means the results or impact of what universities do, in particular teaching and research. The new terminology speaks of price and competition, inputs and outputs, resources, cost and benefits, demand and supply, provider and customer, consumers and investors, quality control and accountability. Education, and post-secondary education especially are increasingly seen as matters for markets. Formal post-secondary education becomes a service, commercialized and traded across national borders. This volume on changing relationship between state and market, contains, besides an introductory analytic overview of the issues, accounts from different countries, regions, and thematic perspectives. Chapter authors describe and analyze government reforms and other developments that have directly or indirectly affected this relationship. Although the geographical focus is on North America, especially Mexico, South East Asia and Europe, the phenomenon is not limited to these regions and countries but worldwide.
SpringerLink eBooks.
Keywords: Education; Education; Education, general; Education (general).